Accounting Information Systems, The Quality of Financial Statements and Internal Control Systems as a Moderation Variable - Yudi Jemiran (CONTABILITA : Journal of Accounting and Finance, 2025)
This study aims to determine the effect of Accounting Information Systems on the quality of Financial Statements in moderation by the Internal Control System. The population in this study is the entire SKPD in Denpasar City Government. Sample determination is done by Purposive sampling method. This study used primary data. Respondents in this study amounted to 83 respondents. The method of data analysis used is Moderated Regression Analysis. The results showed that Accounting Information Systems have a positive effect on the quality of financial statements but the Internal Control System is moderate the influence of Accounting Information Systems on the quality of financial statements